1995
DOI: 10.4315/0362-028x-58.5.482
|View full text |Cite
|
Sign up to set email alerts
|

Performance Characteristics and Microbiological Aspects of Broilers Fed Diets Supplemented with Organic Acids

Abstract: The effects of supplementation of broiler diets with organic acids on live performance and microbiological parameters were evaluated in a series of experiments. In three trials lactic acid (LA) (0.25 to 2.00%) or fumaric acid (FA) (0.5 to 2.00%), and in two trials a formic/propionic acid blend (FP) (.125 to 1.00%) or citric acid (CA) (0.25 to 2.00%) was continually fed to broilers that were inoculated via the drinking water with 108 to 109 CFU/ml nalidixic acid–resistant Salmonella typhimurium (NAL-SAL) on day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
10

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 0 publications
1
31
0
10
Order By: Relevance
“…There were no significant interactions of DFA and OAB for growth performance. Similarly, previous researchers (Izat et al 1990;Waldroup et al 1995) also reported no effect on BW of broiler chicken with the use of formate and propionic acid in the broiler diet. However, Vogt et al (1982) and Skinner et al (1991) …”
Section: Growth Performancementioning
confidence: 94%
“…There were no significant interactions of DFA and OAB for growth performance. Similarly, previous researchers (Izat et al 1990;Waldroup et al 1995) also reported no effect on BW of broiler chicken with the use of formate and propionic acid in the broiler diet. However, Vogt et al (1982) and Skinner et al (1991) …”
Section: Growth Performancementioning
confidence: 94%
“…The finding that MC emulsions containing TW40 kill Salmonella and E. coli in buffer at pH 5 or lower opens the possibility of utilizing MC emulsions in the control of food-borne infections caused by these bacteria. It is of interest that a number of studies have been done on the effect of organic acids, such as lactic acid, in reducing the number of Salmonella and C. jejuni bacteria on chicken carcasses (9, 13) or in diminishing intestinal colonization of Salmonella in chickens (11,20). Since there seems to be a synergistic effect of MC and acid in killing these bacteria as well as Campylobacter, a combination of MC and organic acids might be a feasible approach, e.g., as an additive to feeds or for rinsing carcasses.…”
Section: Discussionmentioning
confidence: 99%
“…One approach is to prevent infection in broiler chickens by eliminating Campylobacter or Salmonella from their drinking water by the addition of chemicals such as chlorine (22) or organic acids at low pH (7). Another approach is to reduce the levels of bacterial colonization in the intestinal tracts of broilers by the addition of chemicals to their feeds (11,20), by competitive inhibition with other bacterial strains (2), or by phage therapy (19). Many attempts to treat poultry carcasses in the slaughterhouse with antibacterial chemicals have been made, but with various results (12,22).…”
mentioning
confidence: 99%
“…in caecal contents following addition of either 0.36% calcium formate or 0.5% formic acid. Waldroup et al (1995), in contrast, found that formic and propionic acid blend, citric, lactic, fumaric acid in concentrations up to 2% offered no protection for Salmonella tymphimurium caecal colonisation. In the last decade, butyric acid was intensively studied for its role in Salmonella infections in poultry.…”
Section: Organic Acids Against Important Poultry Pathogensmentioning
confidence: 99%